Ecologia histórica aplicada à gestão ambiental comunitária da terra indígena Maxakali, Minas Gerais - Marco Túlio da Silva Ferreira (2012)
Throughout the last centuries, socio-cultural diversity loss has been accompanied side by side by global genetic (human and non-human) diversity erosion. The indigenous peoples whose languages belong to the maxakali linguistic family have witnessed the historical process ofenvironmental destruction that still takes place in the Brazilian Atlantic rainforest. Not only confronted with extremely reduced forested areas, the extant pan-maxakali descendants are faced with a severely small territory, which jeopardizes their nomadic habits and swidden agriculture, and greatly endangers environmental quality of the area. The introduction, in the area, of African guinea-grass (Megathyrsus maximus (Jacq.) B.K.Simon & S.W.L.Jacobs Poaceae) and its fire management techniques by the cattle breeder hegemonic surrounding society has forced the maxakali to have to live together and manage this invasive species, often using fire to control it. However, instead of decreasing its abundance, the fire regime management developed by the maxakali (which has striking differences between the one practiced by cattle breeders) has been causing severe environmental damage, whilst favoring the expansion of fire-prone guinea-grass areas when fire hits forest borders, a process which has annually diminishing already impoverished local biodiversity. Absence of the physical forest may bring significant impacts in their symbolic ecology, in which the inter-generational loss of environmental knowledge is the most salient. Therefore, the maxakali presently face the dilemma of adapting their ecological and economical practices of biodiversity landscape management and symbolic interpretation (which are nomadic, extensive, and highly dependent on large forested areas) to a territory that is presently insufficient to meet the demands of a rapidly expanding population. Thus, it becomes necessary to perform an agroecologicalsensibilization towards these people, in order to catalyze a process of community-based environmental and territorial management, aimed at preserving the resources of which their culture depends, both symbolic and materially. Nevertheless, to make this possible with direct intellectual involvement by the main stakeholders (that is, the maxakali), it is first necessary to comprehend this unique cultures Ecology (both as scientia and as praxis), in a way that it may be reflected in a long-term environmental management strategic planning for the protectedarea. In this sense, the present study is aimed at bringing a description of the Maxakali Ecology that may later contribute for a community-based environmental management plan of the Maxakali indigenous territory.